2022
DOI: 10.1093/geroni/igac023
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Model for Encouraging the General Public to Exhibit Helping Behaviors Toward People Living With Dementia

Abstract: Background and Objectives Dementia awareness initiatives aim to promote helping behaviors towards people living with dementia. We applied the bystander intervention process model in the context of the general public’s helping behaviors towards people living with dementia, and we sought to identify the mechanisms underlying the association between dementia knowledge and helping behaviors. Research Design and Methods In a surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Meanwhile, more knowledge of dementia was associated with both a little helping behaviour and advanced helping behaviour. These results are consistent with previous studies that revealed the associations between knowledge/attitudes and the helping behaviours of community members towards PLWD 7,8,10 . Our results also suggest that dementia knowledge and interactions with PLWD could promote in‐depth advanced helping behaviours in addition to attitude improvement by reducing dementia‐related stigma.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Meanwhile, more knowledge of dementia was associated with both a little helping behaviour and advanced helping behaviour. These results are consistent with previous studies that revealed the associations between knowledge/attitudes and the helping behaviours of community members towards PLWD 7,8,10 . Our results also suggest that dementia knowledge and interactions with PLWD could promote in‐depth advanced helping behaviours in addition to attitude improvement by reducing dementia‐related stigma.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies that revealed the associations between knowledge/attitudes and the helping behaviours of community members towards PLWD. 7,8,10 Our results also suggest that dementia knowledge and interactions with PLWD could promote in-depth advanced helping behaviours in addition to attitude improvement by reducing dementia-related stigma. While this study did not specifically investigate ageist attitudes or interactions with older adults without dementia, these could also influence helping behaviours and should therefore be investigated in future research.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The said intention was measured using four vignettes in which local residents encountered a PLWD requiring help. The vignettes were drawn from previous interviews with PLWD, and their families and have shown good validity and reliability in our previous study (Matsumoto et al., 2022). One example of the vignettes is that ‘ One day in mid‐summer, you met an older woman wearing a heavy coat ’.…”
Section: Methodsmentioning
confidence: 99%